Endoplasmic Reticulum Protein Quality Control Failure in Myelin Disorders - Volpi, Vera G.; Touvier, Thierry; D'Antonio, Maurizio (Frontiers in Molecular Neuroscience, 2017)
Abstract Reaching the correct three-dimensional structure is crucial for the proper function of a protein. The endoplasmic reticulum (ER) is the organelle where secreted and transmembrane proteins are synthesized and folded. To guarantee high fidelity of protein synthesis and maturation in the ER, cells have evolved ER-protein quality control (ERQC) systems, which assist protein folding and promptly degrade aberrant gene products. Only correctly folded proteins that pass ERQC checkpoints are allowed to exit the ER and reach their final destination. Misfolded glycoproteins are detected and targeted for degradation by the proteasome in a process known as endoplasmic reticulum-associated degradation (ERAD). The excess of unstructured proteins in the ER triggers an adaptive signal transduction pathway, called unfolded protein response (UPR), which in turn potentiates ERQC activities in order to reduce the levels of aberrant molecules. When the situation cannot be restored, the UPR drives cells to apoptosis. Myelin-forming cells of the central and peripheral nervous system (oligodendrocytes and Schwann cells) synthesize a large amount of myelin proteins and lipids and therefore are particularly susceptible to ERQC failure. Indeed, deficits in ERQC and activation of ER stress/UPR have been implicated in several myelin disorders, such as Pelizaeus-Merzbacher and Krabbe leucodystrophies, vanishing white matter disease and Charcot-Marie-Tooth neuropathies. Here we discuss recent evidence underlying the importance of proper ERQC functions in genetic disorders of myelinating glia.